The sensitivity of reconstructed carbon dioxide concentrations to stomatal preparation methods using a leaf gas exchange model - Michael D. Machesky; Nathan D. Sheldon; Michael T. Hren; Selena Y. Smith (Applications in Plant Sciences)
Abstract Premise Mechanistic models using stomatal traits and leaf carbon isotope ratios to reconstruct atmospheric carbon dioxide (CO2) concentrations (ca) are important to understand the Phanerozoic paleoclimate. However, methods for preparing leaf cuticles to measure stomatal traits have not been standardized. Methods Three people measured the stomatal density and index, guard cell length, guard cell pair width, and pore length of leaves from the same Ginkgo biloba, Quercus alba, and Zingiber mioga leaves growing at known CO2 levels using four preparation methods: fluorescence on cleared leaves, nail polish, dental putty on fresh leaves, and dental putty on dried leaves. Results There are significant differences between trait measurements from each method. Modeled ca calculations are less sensitive to method than individual traits; however, the choice of assumed carbon isotope fractionation also impacted the accuracy of the results. Discussion We show that there is not a significant difference between ca estimates made using any of the four methods. Further study is needed on the fractionation due to carboxylation of ribulose bisphosphate (RuBP) in individual plant species before use as a paleo‐CO2 barometer and to refine estimates based upon widely applied taxa (e.g., Ginkgo). Finally, we recommend that morphological measurements be made by multiple observers to reduce the effect of individual observational biases.